What is in your cup of tea? DNA Verity Test to characterize black and green commercial teas. - Olga De Castro; Maria Comparone; Antonietta Di Maio; Emanuele Del Guacchio; Bruno Menale; Jacopo Troisi; Francesco Aliberti; Marco Trifuoggi; Marco Guida (PLoS ONE, 2017)
In this study, we used several molecular techniques to develop a fast and reliable protocol (DNA Verity Test, DVT) for the characterization and confirmation of the species or taxa present in herbal infusions. As a model plant for this protocol, Camellia sinensis, a traditional tea plant, was selected due to the following reasons: its historical popularity as a (healthy) beverage, its high selling value, the importation of barely recognizable raw product (i.e., crushed), and the scarcity of studies concerning adulterants or contamination. The DNA Verity Test includes both the sequencing of DNA barcoding markers and genotyping of labeled-PCR DNA barcoding fragments for each sample analyzed. This protocol (DVT) was successively applied to verify the authenticity of 32 commercial teas (simple or admixture), and the main results can be summarized as follows: (1) the DVT protocol is suitable to detect adulteration in tea matrices (contaminations or absence of certified ingredients), and the method can be exported for the study of other similar systems; (2) based on the BLAST analysis of the sequences of rbcL+matK±rps7-trnV(GAC) chloroplast markers, C. sinensis can be taxonomically characterized; (3) rps7-trnV(GAC) can be employed to discriminate C. sinensis from C. pubicosta; (4) ITS2 is not an ideal DNA barcode for tea samples, reflecting potential incomplete lineage sorting and hybridization/introgression phenomena in C. sinensis taxa; (5) the genotyping approach is an easy, inexpensive and rapid pre-screening method to detect anomalies in the tea templates using the trnH(GUG)-psbA barcoding marker; (6) two herbal companies provided no authentic products with a contaminant or without some of the listed ingredients; and (7) the leaf matrices present in some teabags could be constituted using an admixture of different C. sinensis haplotypes and/or allied species (C. pubicosta).